An assessment of the multifactorial profile of steroid-metabolizing enzymes and steroid receptors in the eutopic endometrium during moderate to severe ovarian endometriosis - G. Anupa; Jai Bhagwan Sharma; Kallol K. Roy; Jayasree Sengupta; Debabrata Ghosh (BMC, 2019)
Abstract Background Previous studies of expression profiles of major endometrial effectors of steroid physiology in endometriosis have yielded markedly conflicting conclusions, presumably because the relative effects of type of endometriosis, fertility history and menstrual cycle phases on the measured variables were not considered. In the present study, endometrial mRNA and protein levels of several effectors of steroid biosynthesis and action in patients with stage III-IV ovarian endometriosis (OE) with known fertility and menstrual cycle histories were compared with the levels in control endometrium to test this concept. Methods Endometrial samples were collected from patients without endometriosis (n = 32) or OE stages III-IV (n = 52) with known fertility and cycle histories. qRT-PCR and immunoblotting experiments were performed to measure levels of NR5A1, STAR, CYP19A1, HSD17Bs, ESRs and PGR transcripts and proteins, respectively. Tissue concentrations of steroids (P4, T, E1 and E2) were measured using ELISAs. Results The levels of expression of aromatase and ERβ were lower (P < 0.0001) and 17β-HSD1 (P < 0.0001) and PRA (P < 0.01) were higher in OE endometrium. Lower aromatase levels and higher 17β-HSD1 levels were detected in fertile (aromatase: P < 0.05; 17β-HSD1: P < 0.0001) and infertile (aromatase: P < 0.0001; 17β-HSD1: P < 0.0001) OE endometrium than in the matched control tissues. Both proliferative (PP) and secretory (SP) phase OE samples expressed aromatase (P < 0.0001) and ERβ (PP: P < 0.001; SP: P < 0.01) at lower levels and 17β-HSD1 (P < 0.0001) and PRA (PP: P < 0.01; SP: P < 0.0001) at higher levels than matched controls. Higher 17β-HSD1 (P < 0.01) and E2 (P < 0.05) levels and a lower (P < 0.01) PRB/PRA ratio was observed in infertile secretory phase OE endometrium than in control. Conclusions We report that dysregulated expression of 17β-HSD1 and PGR resulting in hyperestrogenism and progesterone resistance during the secretory phase of the menstrual cycle, rather than an anomaly in aromatase expression, was the hallmark of eutopic endometrium from infertile OE patients. Furthermore, the results provide proof of concept that the fertility and menstrual cycle histories exerted relatively different effects on steroid physiology in the endometrium from OE patients compared with the control subjects.